2022
DOI: 10.1177/09544119221122012
|View full text |Cite
|
Sign up to set email alerts
|

Role of Artificial Intelligence and Machine Learning in the prediction of the pain: A scoping systematic review

Abstract: Artificial Intelligence in healthcare is growing quickly in diagnostics and treatment management. Despite the quantity and variety of studies its role in clinical care is not clear. To identify the evidence gaps and characteristics of the Artificial Intelligence and Machine Learning techniques in predicting/diagnosing the pain? Pubmed/Embase were searched from the inception to October 2021 for articles without any language restrictions specifically addressing the following: the accuracy of AI in pain consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…25 However, despite the promising nature of this innovation, it is a growing field, and it is necessary to evaluate and synthesize the available evidence on its current use in the biopsychosocial management of chronic pain. Previous reviews have focused on the use of AI interventions in pain assessment, diagnosis, and prediction, [29][30][31][32][33][34][35][36] while some have explored the management of specific conditions such as low back pain. 35 Zhang et al 21 Moreover, the developing nature of this field implies that research is rapidly ongoing, and newer evidence may now exist.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…25 However, despite the promising nature of this innovation, it is a growing field, and it is necessary to evaluate and synthesize the available evidence on its current use in the biopsychosocial management of chronic pain. Previous reviews have focused on the use of AI interventions in pain assessment, diagnosis, and prediction, [29][30][31][32][33][34][35][36] while some have explored the management of specific conditions such as low back pain. 35 Zhang et al 21 Moreover, the developing nature of this field implies that research is rapidly ongoing, and newer evidence may now exist.…”
Section: Original Manuscriptmentioning
confidence: 99%
“…Different ML models, such as ANNs, linear regression, support vector regression, Support Vector Machines (SVMs), random forest, adaptive boosting, and extreme gradient boosting, are built using extracted features. However, studies showed SVM and DL are more accurate models for the classification of pain [57,58]. Probabilistic models, such as Gaussian Naive Bayes (GNB) classifiers and hidden Markov models (HMMs), can help clinicians assess pain levels with patient self-reports by analyzing physiological information from individuals with chronic pain, including respiration rate, pulse rate, oxygen level, body temperature, and blood pressure [59].…”
Section: Ai-based Pain Assessmentmentioning
confidence: 99%
“…: genetics, environment, patient vitals) and clinical outcomes, learn the relationships that exist, and use this information to predict future outcome in similar patients [16]. In a medical context, AI has been touted to be used in conjunction with electronic medical records (EMR) to help make medical predictions [17][18][19]. Machine learning (ML) is a subset of AI that uses prediction models and algorithms to analyze and draw inferences from patterns of data to learn or adapt.…”
Section: Introductionmentioning
confidence: 99%